2014
DOI: 10.1111/jgs.12891
|View full text |Cite
|
Sign up to set email alerts
|

2012 American Geriatrics Society Beers Criteria: Enhanced Applicability for Detecting Potentially Inappropriate Medications in European Older Adults? A Comparison with the Screening Tool of Older Person's Potentially Inappropriate Prescriptions

Abstract: The 2012 Beers criteria detected the highest number of PIMs, and given the scant overlapping with the STOPP criteria, the use of both tools may be seen as complementary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
74
6
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 46 publications
15
74
6
14
Order By: Relevance
“…Resultados semelhantes têm sido observados em investigações internacionais 30,31,32 e brasileiras 23,24,36 . Como já relatado em estudos anteriores, a polifarmácia tem sido associada a resultados negativos em saúde, como, por exemplo, reações adversas, interações medicamentosas, baixa adesão e síndromes geriátricas 9,37,38 .…”
Section: Métodosunclassified
“…Resultados semelhantes têm sido observados em investigações internacionais 30,31,32 e brasileiras 23,24,36 . Como já relatado em estudos anteriores, a polifarmácia tem sido associada a resultados negativos em saúde, como, por exemplo, reações adversas, interações medicamentosas, baixa adesão e síndromes geriátricas 9,37,38 .…”
Section: Métodosunclassified
“…Among identified adverse drug events, preventable adverse drug events have been reported to be 27% in primary care and 42% in long-term care, where prescribing and monitoring stages of pharmaceutical care were emphasized for prevention of adverse drug events (6,7). Potentially inappropriate medications have been identified in Beers Criteria (8), which aimed to prevent poor outcomes in elderly patients such as ADRs, hospitalization, morbidity, or mortality (8). In the elderly population DDIs can be diagnosed as severe adverse outcomes (9).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported high prevalence of prescription of non-steroid anti-inflammatory drugs (NSAIDs) detected by 2008 STOPP (Ubeda et al, 2012;Blanco-Reina et al, 2014;Vezmar Kovačević et al, 2014). Even though the international guidelines continue to indicate low-dose aspirin for reducing cardiovascular risk, this benefit may not overcome the risk of gastrointestinal bleeding in older patients (Lanas, Polo-Tomás, CasadoArroyo, 2013;Ikeda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Amitriptyline was considered a PIM in a few cases by both criteria, while aspirin was a major PIM according to 2008 STOPP but a minor PIM by 2003 Beers. It has been suggested that the use of both 2012 Beers and 2008 STOPP may be complementary to detect PIMs in older adults (Blanco-Reina et al, 2014). However, a general guideline including these lists may not be suitable for all populations, considering that the medications approved for commercialization may differ between countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation